2015
DOI: 10.4239/wjd.v6.i6.868
|View full text |Cite
|
Sign up to set email alerts
|

Effect of diabetes mellitus on sleep quality

Abstract: Diabetes mellitus (DM) is a highly prevalent condition affecting about 347 million people worldwide. In addition to its numerous clinical implications, DM also exerts a negative effect on patient's sleep quality. Impaired sleep quality disrupts the adequate glycemic control regarded as corner stone in DM management and also lead to many deleterious effects causing a profound impact on health related quality of life. This article outlines various factors leading to impaired sleep quality among diabetics and del… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
75
0
6

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 108 publications
(88 citation statements)
references
References 40 publications
7
75
0
6
Order By: Relevance
“…The NOC survey results indicated that sleep was a problem for a large number (43%) of our participants. Poor sleep quality can be due to numerous reasons including; nocturia, polyuria, neuropathy pain, obstructive sleep apnea, hypertension [65]. There is still an uncertainty as to what causes poor sleep quality.…”
Section: Discussionmentioning
confidence: 99%
“…The NOC survey results indicated that sleep was a problem for a large number (43%) of our participants. Poor sleep quality can be due to numerous reasons including; nocturia, polyuria, neuropathy pain, obstructive sleep apnea, hypertension [65]. There is still an uncertainty as to what causes poor sleep quality.…”
Section: Discussionmentioning
confidence: 99%
“…Diabetes mellitus is being increasingly recognized as a worldwide significant public health problem (14). Patients with diabetes mellitus, by virtue of its numerous clinical and associated implications, suffer a poor quality of life.…”
Section: Discussion:-mentioning
confidence: 99%
“…31 Sleep quality is also affected by diabetes. [32][33][34] Diabetes is an independent risk factor for EDS and altered sleep quality regardless of AHI or time with S a O 2 < 90%. 34 Diabetic patients have been found to have significantly more OSA symptoms, more nocturia, and decreased self-rated health.…”
Section: Discussionmentioning
confidence: 99%